Recent Advances in Oral Mucoadhesive Drug Delivery - Shiva Golshani; Alireza Vatanara; Mohsen Amin (Frontiers Media S.A., 2022)
The oral cavity is one of the most important routes for local and systemic drug delivery, as it has a large surface, high permeability, and rich blood supply. Oral mucosal drug delivery has some advantages, such as enhancing bioavailability, preventing first-pass metabolism, reducing dose frequency, and non-invasiveness. In recent years, notable oral mucoadhesive patents were introduced to the pharmaceutical field, which indicates promising potentials for therapeutic purposes. Oral mucosal drug delivery can play a key role to deliver the biological drugs, such as antimicrobial peptides. This article gives an overview of oral mucoadhesive drug delivery systems and provides basic principles for the researchers to overcome the problems associated with the formulation design.